A viable dipole magnet concept with REBCO CORC® wires and further development needs for high-field magnet applications. (6th March 2018) - Wang, Xiaorong; Caspi, Shlomo; Dietderich, Daniel R; Ghiorso, William B; Gourlay, Stephen A; Higley, Hugh C; Lin, Andy; Prestemon, Soren O; van der Laan, Danko; Weiss, Jeremy D
Abstract: REBCO coated conductors maintain a high engineering current density above 16 T at 4.2 K. That fact will significantly impact markets of various magnet applications including high-field magnets for high-energy physics and fusion reactors. One of the main challenges for the high-field accelerator magnet is the use of multi-tape REBCO cables with high engineering current density in magnet development. Several approaches developing high-field accelerator magnets using REBCO cables are demonstrated. In this paper, we introduce an alternative concept based on the canted cos θ (CCT) magnet design using conductor on round core (CORC ® ) wires that are wound from multiple REBCO tapes with a Cu core. We report the development and test of double-layer three-turn CCT dipole magnets using CORC ®  wires at 77 and 4.2 K. The scalability of the CCT design allowed us to effectively develop and demonstrate important magnet technology features such as coil design, winding, joints and testing with minimum conductor lengths. The test results showed that the CCT dipole magnet using CORC ®  wires was a viable option in developing a REBCO accelerator magnet. One of the critical development needs is to increase the engineering current density of the 3.7 mm diameter CORC ®  wire to 540 A mm −2  at 21 T, 4.2 K and to reduce the bending radius to 15 mm. This would enable a compact REBCO dipole insert magnet to generate a 5 T field in a background field of 16 T at 4.2 K.